Shutter Island - Lehane, Dennis (New York Harper Torch, 2003)
U.S. Marshal Teddy Daniels travels to Shutter Island, home of Ashecliffe Hospital for the Criminally Insane, to find an escaped patient and to investigate rumors of their radical approach to psychiatry.
Keywords: Massachusetts